The Influence of Store Atmosphere, Service Quality, and Product Variance on Customer Loyalty Through Customer Satisfaction at Marinor Cafe in Makassar City - Sriyanti, Andi Hikmah Dewi; Payangan, Otto R.; Mustafa, Fahrina (Economics and Business Journal (ECBIS), 2023)
Through customer satisfaction at Marinar Café Makassar City, this study aims to analyze the effect of store atmosphere, service quality, and product variants on consumer loyalty. This study uses a quantitative approach to collect data from 100 respondents who are customers of Marinor Café in Makassar City. Participants in this study were all visitors to the Marinor Cafe in Makassar City. Path analysis (Path analysis) is the data analysis method used. The findings show that customer satisfaction at Marinor Café Makassar City is positively and significantly influenced by store atmosphere, service quality, and product variants. Therefore, it can be said that customer satisfaction can mediate the effect of service quality and product variety on customer loyalty, but does not mediate the effect of store atmosphere on customer loyalty.